Issues Related to The Distribution Of Inheritance Mass In Various Legal Systems In World Countries - Bekzod Gadoev (Zien Journals, 2024)
This article analyzes the peculiarities of the distribution of the mass of inheritance in various legal systems, as well as the general requirements for inheritance. Also, issues related to the order in which the inheritance should be formed, the application of the right to inheritance are described through the experience of advanced foreign countries.
Keywords: Roman-Germanic family of law; Anglo-Saxon family of law; Muslim family of law